Trypanosoma cruzi Infection at the Maternal-Fetal Interface: Implications of Parasite Load in the Congenital Transmission and Challenges in the Diagnosis of Infected Newborns - Bustos, Patricia L. (2019)
Fil: Bustos, Patricia L. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.